Study Protocol of tDCS Based Pain Modulation in Head and Neck Cancer Patients Under Chemoradiation Therapy Condition: An fNIRS-EEG Study - de Souza Moura, Brenda; Hu, Xiao-Su; DosSantos, Marcos F.; DaSilva, Alexandre F. (Frontiers in Molecular Neuroscience, 2022)
Background: Multiple therapeutic strategies have been adopted to reduce pain, odynophagia, and oral mucositis in patients with head and neck cancer. Among them, transcranial direct current stimulation (tDCS) represents a unique analgesic modality. However, the details of tDCS mechanisms in pain treatment are still unclear. Aims: 1) to study the analgesic effects of a protocol that encompassed supervised-remote and in-clinic tDCS sessions applied in head and neck patients undergoing chemoradiation therapy; 2) to explore the underlining brain mechanisms of such modulation process, using a novel protocol that combined functional near-infrared spectroscopy (fNIRS), and electroencephalograph (EEG), two distinct neuroimaging methods that bring information regarding changes in the hemodynamic as well as in the electrical activity of the brain, respectively. Methods: This proof-of concept study was performed in two subjects. The study protocol included a 7 week-long tDCS stimulation procedure, a pre-tDCS baseline session and two post-tDCS follow-up sessions. Two types of tDCS devices were used. One was used in the clinical setting and the other one remotely. Brain imaging were obtained in the weeks 1, 2, 5, 7, 8, and after one month. Results: The protocol implemented was safe and reliable. Preliminary results of the fNIRS analysis at the weeks 2 and 7 showed a decrease in functional connections between the bilateral prefrontal cortex (PFC) and the primary sensory cortex (S1) (p < 0.05, FDR corrected). Changes in EEG power spectra were found in the PFC, when comparing the seventh with first week of tDCS. Conclusion: The protocol combining remote, and in-clinic administered tDCS and that integrated fNIRS and EEG to evaluate the brain activity is feasible. The preliminary results suggest that the mechanisms of tDCS in reducing the pain of head and neck cancer patients may be related to its effects in the connections between the S1 and the PFC.